Presence of Pseudomonas aeruginosa influences biofilm formation and surface protein expression of Staphylococcus aureus. (25th May 2015) - Kumar, Amit; Ting, Yen Peng
Summary: Although S taphylococcus aureus and P seudomonas aeruginosa can individually colonize and infect their hosts, the commensalistic effect of the two is more tenacious and lethal. In this study, it was shown that in co‐culture with P . aeruginosa, a sub‐population of S . aureus exhibited improved resistance to kanamycin by selection of small colony variant (SCV) phenotype. Additionally, biofilm formation by the two bacteria was denser in the co‐culture, compared with biofilm formed in individual pure cultures. Using Atomic Force Microscope (AFM) force spectroscopy for single cells, it was demonstrated that S . aureus cultured in the presence of P . aeruginosa bound more tenaciously to substrates. Surface‐shaved peptides were isolated and identified using ultra‐performance liquid chromatography‐quadrupole‐time of flight and a homology search programspider . Results indicated that serine‐rich adhesin, extracellular matrix binding protein and other putative adhesion proteins could be responsible for the enhanced attachment of S . aureus in the co‐culture. Besides, several other proteins were differentially expressed, indicating the occurrence of a range of other interactions. Of particular interest was a multidrug resistant protein named ABC transporter permease which is known to expel xenobiotics out of the cells. Positive regulation of this protein could be involved in the SCV selection of S . aureus in the co‐culture.